Analisis Risiko Keselamatan Kerja di Mesin Bubut Menggunakan Metode HIRARC - Nurmahmudi, Nurmahmudi; Rifelino, Rifelino; Nabawi, Rahmat Aziz; Irzal, Irzal (Al-DYAS, 2024)
HIRARC is a series of processes to identify hazards, assess risks, and control risks in work activities. In the context of this research, the author analyzes the safety risks in the machining engineering workshop of SMK Negeri 1 Lembah Melintang using the HIRARC method. This method aims to prevent and reduce workplace accidents and control risks appropriately. This research is descriptive with a qualitative approach. Data sources include primary and secondary data. Data collection techniques involve field observations, interviews, and analysis of standard operating procedure documents in the machining engineering program of SMK Negeri 1 Lembah Melintang. The results show that the level of safety risk in the machining engineering workshop of SMK Negeri 1 Lembah Melintang is at a low level based on the HIRARC method. The risk analysis helps identify potential hazards, assess related risks, and design risk control measures to create a safer working environment.